Bridging Waqf and Sukuk: Cross-Country Insights from Indonesia and Malaysia on Islamic Social Finance Innovation - Mufti Afif; Syahruddin; Khurun’in Zahro’; Nur Suriana Awaludin (MUSLIM HERITAGE, 2025)
Abstract The integration of waqf and sukuk is a strategic innovation in productive waqf management to support socio-economic development. Indonesia and Malaysia, as two countries with the largest Muslim populations and rapidly growing Islamic financial infrastructures, are relevant case studies to explore the implementation of this model. This research aims to examine sukuk-based productive waqf management in Indonesia and Malaysia, highlighting the challenges, potentials, and implementation of the integration model. This research utilizes a descriptive qualitative method with a phenomenological approach. The results show that waqf-based sukuk is a strategic innovation to optimize waqf assets and promote Islamic economic growth. However, its implementation still faces obstacles in the form of structural complexity, the need for regulatory harmonization, and low investor awareness. Waqf-based sukuk faces challenges in the form of structural complexity that requires careful planning and regulatory compliance that requires a harmonized legal framework. Low investor awareness of the instrument is also an obstacle to increasing its widespread adoption.   Abstrak Integrasi wakaf dan sukuk merupakan inovasi strategis dalam pengelolaan wakaf produktif untuk mendukung pembangunan sosial-ekonomi. Indonesia dan Malaysia, sebagai dua negara dengan populasi Muslim terbesar dan infrastruktur keuangan syariah yang berkembang pesat, menjadi studi kasus yang relevan untuk mengeksplorasi implementasi model ini. Penelitian ini bertujuan mengkaji pengelolaan wakaf produktif berbasis sukuk di Indonesia dan Malaysia, dengan menyoroti tantangan, potensi, dan implementasi model integrasi tersebut. Penelitian ini menggunakan metode kualitatif deskriptif dengan pendekatan fenomenologi. Hasil penelitian menunjukkan bahwa sukuk berbasis wakaf merupakan inovasi strategis untuk mengoptimalkan aset wakaf dan mendorong pertumbuhan ekonomi Syariah. Namun, implementasinya masih menghadapi hambatan berupa kompleksitas struktural, kebutuhan harmonisasi regulasi, dan rendahnya kesadaran investor. Sukuk berbasis wakaf menghadapi tantangan berupa kompleksitas struktur yang memerlukan perencanaan matang dan kepatuhan terhadap regulasi yang membutuhkan kerangka hukum harmonis. Rendahnya kesadaran investor terhadap instrumen ini juga menjadi hambatan dalam meningkatkan adopsi secara luas. Keywords: Integrasi Wakaf; Sukuk; Wakaf Produktif; Indonesia; Malaysia.